RESPONS STRUKTUR PERKERASAN JALAN KOMPOSIT AKIBAT BEBAN LALU LINTAS DENGAN METODE ELEMEN HINGGA DI KABUPATEN MERAUKE - Bartolomeus Krimanto Pauta; Bambang Suhendro; Latif Budi Suparma (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2022)
Abstract Tanah Miring–Kurik Road, Merauke is one of the national roads in Merauke Regency which has been reconstructed into composite pavement. Composite pavement is a combination of flexible pavement and rigid pavement. This study aims to determine the response of composite pavement structures due to vehicle loading and the effect of temperature on pavement. The response analysis of road pavement structures was carried out using the finite element method, using the SAP 2000 computer program. Pavements are idealized in 2 analysis models, namely the slab model on elastic foundations and the 3D Solid model. From the results of the analysis on the plate model on an elastic foundation, the maximum tensile stress that occurs in the concrete slab is 2.081 MPa at 6% subgrade CBR. The maximum tensile stress produced by the 3 Dimensional Solid model is 2.510 MPa. The pavement can withstand stresses due to the combined effects of temperature and vehicle loading up to a temperature gradient of 6°C on the subgrade CBR of 6%. The Hot Rolled Sheet layer can reduce the maximum tensile stress in concrete slabs by up to 9.7%, for slab models on elastic foundations, and 9%, for 3 Dimensional Solid models. Keywords: composite pavement; road pavement; pavement structure response; finite element method. Abstrak Jalan Tanah Miring–Kurik, Merauke adalah salah satu jalan nasional di Kabupaten Merauke yang telah direkonstruksi menjadi perkerasan komposit. Perkerasan komposit merupakan kombinasi antara perkersan lentur dan perkerasan kaku. Penelitian ini bertujuan untuk mengetahui respons struktur perkerasan komposit akibat pembebanan kendaraan dan pengaruh temperatur pada perkerasan. Analisis respons struktur perkerasan jalan dilakukan dengan menggunakan metode elemen hingga, dengan memanfaatkan program komputer SAP 2000. Perkerasan diidealisasikan dalam 2 model analisis, yaitu model pelat pada fondasi elastis dan model Solid 3 Dimensi. Dari hasil analisis pada model pelat pada fondasi elastis, diperoleh tegangan tarik maksimum yang terjadi pada slab beton adalah 2,081 MPa pada CBR tanah dasar 6%. Tegangan tarik maksimum yang dihasilkan model Solid 3 Dimensi sebesar 2,510 MPa. Perkerasan dapat menahan tegangan akibat pengaruh kombinasi temperatur dan pembebanan kendaraan hingga pada gradien temperatur permukaan dan dasar perkerasan sebesar 6°C pada CBR tanah dasar 6%. Lapisan Hot Rolled Sheet dapat mengurangi tegangan tarik maksimal pada pelat beton hingga 9,7%, pada model pelat pada fondasi elastis, dan 9%, untuk model Solid 3 Dimensi. Kata-kata kunci: perkerasan komposit; perkerasan jalan; respons struktur perkerasan; metode elemen hingga